Decoding structural determinants of aryl hydrocarbon receptor antagonism by monoterpenoids - Zůvalová, Iveta; Vyhlídalová, Barbora; Ondrová, Karolína; Nádvorník, Petr; Hrubý, Jiří; Illés, Peter; Soural, Miroslav; Šebela, Marek; Šindlerová, Lenka; Kubala, Lukáš; Mani, Sridhar; Dvořák, Zdeněk (Bioorganic chemistry, 2025)
Monocyclic monoterpenoids carvones have been recently identified as atypical negative allosteric modulators of aryl hydrocarbon receptor (AhR). In the current work, we performed AhR antagonist activity screening of 100 natural and synthetic monoterpenoids, and their analogues. Using SAR approach, structural determinants of AhR antagonist activity were assigned, including CO presence/position, planarity, and C3/C5-alkylation. Applying pyramidal selection criteria, including absence of residual agonist activity, no cytotoxicity, strong antagonist potency, and pan-antagonism against diverse AhR agonists, we distilled four lead AhR antagonists (carvacrol, o-cresol, 3-methyl-S-carvone, EN-2). Whereas 3-methyl-S-carvone and EN-2 were non-competitive AhR pan-antagonists, carvacrol and o-cresol were ligand-selective AhR antagonists acting by unclear mechanism. We characterized in detail the effects of lead compounds at cellular functions of AhR, including AhR nuclear translocation, AhR dimerization with ARNT, and the expression of AhR-regulated genes. As a proof of concept, effects of monoterpenoids in the murine macrophages were investigated.
Keywords: Mice; Molecular Structure; Dose-Response Relationship, Drug; molekulární struktura; Monoterpenes; vztah mezi dávkou a účinkem léčiva; Animals; myši; Humans; lidé; receptory aromatických uhlovodíků; zvířata; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Receptors, Aryl Hydrocarbon; monoterpeny